Flexicurity and political philosophy - Tangian, Andranik S. (New York, 2011)
"Flexicurity is a European labour market policy adopted in 2007 within the European Employment Strategy. This policy aims at combining the ongoing flexibilization of employment relations with the traditions of the European welfare state. This book examines and summarizes thirty empirical studies in flexicurity written by the author in 2004 and 2010. The book provides empirical evidence of increasing labour flexibility accompanied by a decline of social security. The author also shows that the countries with higher flexibility are more affected by the crisis. This is a serious warning against improper implementation of flexicurity and its one-sided use in favour of employers."